2017
DOI: 10.1093/ntr/ntx028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Switching to the Menthol Tobacco Heating System 2.2, Smoking Abstinence, or Continued Cigarette Smoking on Clinically Relevant Risk Markers: A Randomized, Controlled, Open-Label, Multicenter Study in Sequential Confinement and Ambulatory Settings (Part 2)

Abstract: IntroductionModified-risk tobacco products are expected to reduce exposure to harmful and potentially harmful constituents of cigarette smoke, and ultimately reduce the health burden of smoking-related diseases. Clinically relevant risk markers of smoking-related diseases inform about the risk profile of new tobacco products in the absence of in-market epidemiological data. The menthol Tobacco Heating System 2.2 (mTHS) is a modified-risk tobacco product in development as an alternative to cigarettes (conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 27 publications
4
90
1
3
Order By: Relevance
“…Brossard et al showed that the nicotine pharmacokinetic profile of IQOS was close to that of conventional cigarettes with similar urge-tosmoke levels [36]. The use of IQOS or glo reduced the exposure to smoke toxicants in a manner comparable to quitting tobacco use [74,75]. After switching from conventional cigarettes to HTPs (IQOS or glo), a significant reduction in the levels of biomarkers of exposure to harmful and potentially harmful constituents was observed [76][77][78].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Brossard et al showed that the nicotine pharmacokinetic profile of IQOS was close to that of conventional cigarettes with similar urge-tosmoke levels [36]. The use of IQOS or glo reduced the exposure to smoke toxicants in a manner comparable to quitting tobacco use [74,75]. After switching from conventional cigarettes to HTPs (IQOS or glo), a significant reduction in the levels of biomarkers of exposure to harmful and potentially harmful constituents was observed [76][77][78].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 99%
“…The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78]. However, there have been no independent studies regarding short-term and longterm health consequences of HTP use.…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%
“…The level of HDL-C was not significantly different between the NCIT group and the CC1 group (p ¼ 0.4293). Although, three previous-reported clinical studies showed that there was a statistically significant increase of HDL-C in the NVP (Electrically Heated Cigarette Smoking System (EHCSS/ EHCSS-K6/electric cigarette) group compared with the CC group (Roethig et al 2008, Cravo et al 2016, Ludicke et al 2018, other studies did not show this (Ogden et al 2015, Walele et al 2018. Therefore, the changes in HDL-C levels after switching to NVPs were not consistent.…”
Section: Differences In Boph At Day 28/29mentioning
confidence: 94%
“…In order to assess health outcomes, studies to identify biomarkers of potential harm (BoPH) associated with oxidative stress, inflammation, lipid metabolism, glucose metabolism and pulmonary functions have been conducted using smokers (SM) and nonsmokers (NS) (Burchfiel et al 1995, Prieme et al 1998, Eliasson et al 2001, Minami et al 2002, Polidori et al 2003, Flores et al 2004, Wannamethee et al 2005, Halvorsen et al 2007, Ludicke et al 2015, Ogden et al 2015. Although, there are many clinical studies on BoE using NVPs, there are few studies on BoPH associated with smoking using NVPs (Roethig et al 2008, Ogden et al 2015, Ludicke et al 2018. In addition, although, some studies have found that exposure to cigarette smoke toxicants (CSTs) with NVPs were significantly reduced compared to conventional cigarettes (CC), the changes in BoPH varied among the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Der Hersteller führte 4 klinische Studien durch, um zu untersuchen, ob sich eine geringere Exposition positiv auf entsprechende Biomarker und gegebenenfalls auf die Entstehung tabakassoziierter Krankheiten auswirkt [6][7][8][9]. Zwei der Studien, die in Polen und Japan durchgeführt wurden, waren stationär durchgeführte 5-tägige Studien [6,7].…”
Section: Klinische Studienunclassified